Postoperative Complications Following Ankle Fractures in the Geriatric Population: A Case Series. Issue 4 (16th October 2019) - Anderson, Matthew; Jha, Aaradhana J.; Naranje, Sameer M.; Viner, Gean C.; McKissack, Haley; Hsu, Alan; Chinnakkannu, Karthikeyan; McGwin, Gerald; Shah, Ashish B.; Moraes, Leonardo V. M.
Category: Ankle, Trauma Introduction/Purpose: Ankle fractures are among the most common orthopedic injuries. While open reduction and internal fixation (ORIF) is the standard treatment for displaced ankle fractures in younger patients, there is controversy regarding the optimal management of these injuries among geriatric patients due to the high prevalence of comorbidities. Closed manipulation leads to poor long-term functional outcomes, with high rates of malunion and non-union in all populations as well as higher mortality in patients over 65 years of age. However, surgical management in the elderly carries rates of complications as high as 20-40%. The purpose of this study was to investigate risk factors for healing complications following ORIF of ankle fractures in patients greater than 75 years of age. Methods: All patients 75 years of age and older undergoing open reduction and internal fixation of ankle fractures at a single institution from 2008 to 2018 were identified. Patients with polytrauma and/or pilon fractures were excluded. Patient medical records were reviewed to obtain information regarding details about the injury, surgery, and follow-up as well as patient demographics and comorbidities. Radiographs from post-operative clinic visits were examined by a foot and ankle certified orthopedic fellow for each patient and the time for complete union was recorded as well as any delayed union or malunion. Fisher's exact tests were used to compare post-operative complications (wound infection, wound dehiscence, sepsis, deep vein thrombosis, revision surgery, and malunion/nonunion) among those with and without specific comorbidities. Results: Patients with other comorbidities had a statistically significant increased risk of revision surgery (p<0.0001). Additionally, those who used illicit drugs had statistically significant increased risk of sepsis (0.0213). Revision surgeries included syndesmotic screw removal, a standard procedure which does not necessarily imply presence of complication. Conclusion: Elderly patients are susceptible to various postoperative complications. Substance abuse is associated with revision surgery, while the presence of other comorbidities collectively is associated with sepsis. To optimize postoperative management, surgeons should be aware of patient comorbidities and exceptionally attentive at follow-up examinations for these patients.